Naphthalene Diimides Prepared by a Straightforward Method and Their Characterization for Organic Electronics. Issue 15 (23rd April 2018) - Korzec, Mateusz; Kotowicz, Sonia; Łaba, Katarzyna; Łapkowski, Mieczysław; Małecki, Jan Grzegorz; Smolarek, Karolina; Maćkowski, Sebastian; Schab‐Balcerzak, Ewa
Abstract : A new approach for the synthesis of acetylene‐substituted naphthalene diimides in polar solvents with PdCl2, Et3 N, and electrolytic copper powder was developed. This simplified approach allows for high‐throughput synthesis, and the reaction products can be readily separated. DFT studies revealed that the electronic structures of these compounds are mainly determined by the central naphthalene diimide unit and the acetylene groups. The obtained thermally stable and soluble compounds undergo reversible reduction with electron affinities of 4.18 to 4.28 eV. They emit green light with photoluminescence quantum yields of ca. 6 % in chloroform and in the range 3–12 % as thin films. The compounds were applied as emitting layers for both nondoped and doped single‐layer organic light‐emitting diodes (OLEDs) fabricated by solution processing. Under an applied external voltage, they exhibit orange or red electroluminescence. Abstract : A new approach for the synthesis of acetylene‐substituted naphthalene diimides is developed. The obtained compounds emit green light with quantum photoluminescence yields of ca. 6 % in chloroform and in the range 3–12 % as thin films. Under an applied external voltage, they exhibit orange or red electroluminescence.